Second Five Year Plan Bombay State Panch Mahals District - Government of Bombay (Government of Bombay, 1958)
The Second Five-Year Plan (1956–1961) for Panch Mahals District in the former Bombay State presents a comprehensive framework for socio-economic development aimed at improving agricultural productivity, infrastructure, education, healthcare, and welfare for marginalized communities. Covering an area of approximately 3,499.2 square miles with a largely rural population of about 1.1 million people distributed across ten talukas and one mahal, the district faced developmental challenges due to its heavy dependence on monsoon-based agriculture and a large proportion of Scheduled Tribes, who constituted nearly 40% of the population. The plan prioritizes agricultural advancement through the introduction of improved seeds, fertilizers, pest control measures, crop demonstrations, and composting practices to enhance crop yields, along with expanded irrigation initiatives intended to increase irrigated land from 6% to 12% of cultivated areas. Major irrigation efforts include projects such as the Mahi (Kadana) Reservoir and several tank schemes designed to irrigate tens of thousands of acres and improve agricultural sustainability. Animal husbandry development complements agricultural growth through improved veterinary services, livestock vaccination, and breeding programs. Infrastructure development focuses on road construction, improved transportation networks, and the establishment of regulated markets to provide farmers with fair pricing and better access to markets. Community development initiatives include the expansion of Village Panchayats, aiming to establish local self-governance structures across all villages, along with numerous local development works such as construction of roads, wells, village halls, culverts, and school buildings. Educational development is another major component, with significant expansion of primary education facilities, promotion of free and compulsory schooling, conversion of schools into craft-based institutions, and the strengthening of teacher training programs. Public health initiatives emphasize the expansion of medical institutions, improved sanitation, safe water supply, and maternal and child welfare services. The plan also addresses housing through cooperative housing schemes and slum clearance programs. Special welfare programs are designed to uplift Scheduled Tribes and other backward classes through grants, subsidies, improved agricultural practices, and educational support. Additionally, land reform measures aim to prevent fragmentation of holdings and strengthen tenancy rights, while forestry initiatives focus on afforestation and sustainable resource management. Overall, the development strategy for Panch Mahals District reflects an integrated and participatory approach to rural development, emphasizing inclusive growth, improved living standards, and long-term economic sustainability.
Panch Mahals District
Panch Mahals District
Keywords: State Five Year Plan; Panch Mahals District Development; Agricultural Development Programs; Minor Irrigation Projects; Scheduled Tribes Welfare; Village Panchayat Expansion; Cottage and Small-Scale Industries; Infrastructure and Road Development; Educational Expansion Programs; Public Health and Sanitation; Land Reforms and Forestry; Community Development Initiatives